A novel approach for enhancement of geometric and contrast resolution properties of low contrast images - Singh K.K.; Bajpai M.K.; Pandey R.K. (My University, 2025)
The present work encompasses a new image enhancement algorithm using newly constructed Chebyshev fractional order differentiator. We have used Chebyshev polynomials to design Chebyshev fractional order differentiator. We have generated the high pass filter corresponding to it. The designed filters are applied for decomposing the input image into four bands and low-low U+0028 L-L U+0029 sub-band is updated using correction coefficients. Reconstructed image with updated L-L sub-band provides the enhanced image. The visual results obtained are encouraging for image enhancement. The applicability of the developed algorithm is illustrated on three different test images. The effects of order of differentiation on the edges of images have also been presented and discussed. © 2014 Chinese Association of Automation.